PHYSICO-CHEMICAL PROPERTIES, RHEOLOGICAL BEHAVIOR AND MINERAL CONTENTS OF HONEY VARIETIES FROM OLTENIA REGION - PĂDURE, Mirabela; TĂMAȘ, Andra; NIȚU, Sabina; RUSU, Gerlinde; NEGREA, Adina; PASCU, Bogdan (Studia Universitatis Babeș-Bolyai Chemia, 2026)
The honey samples analysed in this study were obtained from a private producer located in Olt County who requested a qualitative characterization of his products depending on honey sources. The first stage of the investigation involved key physicochemical parameters: moisture content, free and total acidity, initial and total invert sugars, sucrose levels, and the presence of hydroxymethylfurfural (HMF) and metallic elements. Differential Scanning Calorimetry (DSC) was additionally used to characterize the thermal properties of the samples. The final part of the study examines the rheological behavior of four honey varieties under different temperature conditions, providing insights into their flow characteristics and structural stability. All the obtained values fall within the ranges established by European regulations, except for Pb; the exceedances reflect the influence of anthropogenic factors in the mentioned region.